2018
DOI: 10.1371/journal.pone.0193649
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate and minimally-modified low-density lipoprotein cooperatively promote inflammatory responses in macrophages

Abstract: Increased consumption of Western-type diets and environmental insults lead to wide-spread increases in the plasma levels of saturated fatty acids and lipoprotein oxidation. The aim of this study is to examine whether palmitate and minimally modified low-density lipoprotein (mmLDL) exert an additive effect on macrophage activation. We found that CXCL2 and TNF-α secretion as well as ERK and p38 phosphorylation were additively increased by co-treatment of J774 macrophages with palmitate and mmLDL in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…As a consequence, TLR can be repeatedly activated during multi-day treatment of the cells with this SFA [87]. PA may increase the mRNA expression and protein levels of TLR4, which enhances the signal transduction of this receptor [129131]. It can also support the activation of TLR4.…”
Section: Indirect Effect Of Palmitic Acid On Toll-like Receptors Actimentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, TLR can be repeatedly activated during multi-day treatment of the cells with this SFA [87]. PA may increase the mRNA expression and protein levels of TLR4, which enhances the signal transduction of this receptor [129131]. It can also support the activation of TLR4.…”
Section: Indirect Effect Of Palmitic Acid On Toll-like Receptors Actimentioning
confidence: 99%
“…As a consequence, in macrophages and monocytes, there is an increased expression of cytokines such as IL-1β [85], TNF-α [86, 88], CCL2/monocyte chemoattractant protein-1 (MCP-1) [91, 130, 182], CCL4/macrophage inflammatory protein 1β (MIP-1β) [183] and increase in COX-2 [84, 136] and matrix metallopeptidase 9 (MMP-9) expression [85, 92]. PA also increases the LPS effect on the IL-1β [130], CXCL2 [131] and TNF-α production [130, 131]. However, PA can also induce TNF-α expression independently of TLR4 activation [54].…”
Section: Consequences Of the Proinflammatory Action Of Palmitic Acidmentioning
confidence: 99%
“…Indeed, the collected data showed that plasma lipid SFA level is positively correlated the plasma levels of the CRP, fibrinogen and pro-inflammatory cytokines [ 21 , 22 ]. In fact, SFA seem to stimulate inflammatory responses through immune cell effector activation and recruitment [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…These, become much more responsive under physiologic stimuli which depend on the NLRP3-inflammasome pathway (Christ et al, 2018). Selective lipid species, such as palmitate and stearate, as well as, carbohydrates have been identified to activate the NLRP3inflammasome pathway (Wen et al, 2011;Ann et al, 2018). For instance, saturated lipids from diet intake such as palmitic and stearic acids promote IL-1β release from bone marrowderived macrophages of rodents and humans, respectively (Wen et al, 2011;L'homme et al, 2013), an effect replicated in murine macrophages (Ann et al, 2018).…”
Section: Potential Role Of the Nod-like Receptor Protein 3 Inflammasomentioning
confidence: 99%
“…Selective lipid species, such as palmitate and stearate, as well as, carbohydrates have been identified to activate the NLRP3inflammasome pathway (Wen et al, 2011;Ann et al, 2018). For instance, saturated lipids from diet intake such as palmitic and stearic acids promote IL-1β release from bone marrowderived macrophages of rodents and humans, respectively (Wen et al, 2011;L'homme et al, 2013), an effect replicated in murine macrophages (Ann et al, 2018). Of note, immune activation by palmitic and stearic acids precisely depends on the NLRP3-inflammasome pathway (Wen et al, 2011;L'homme et al, 2013).…”
Section: Potential Role Of the Nod-like Receptor Protein 3 Inflammasomentioning
confidence: 99%